2018
DOI: 10.3389/fcimb.2018.00192
|View full text |Cite
|
Sign up to set email alerts
|

Lipid A Has Significance for Optimal Growth of Coxiella burnetii in Macrophage-Like THP-1 Cells and to a Lesser Extent in Axenic Media and Non-phagocytic Cells

Abstract: Lipid A is an essential basal component of lipopolysaccharide of most Gram-negative bacteria. Inhibitors targeting LpxC, a conserved enzyme in lipid A biosynthesis, are antibiotic candidates against Gram-negative pathogens. Here we report the characterization of the role of lipid A in Coxiella burnetii growth in axenic media, monkey kidney cells (BGMK and Vero), and macrophage-like THP-1 cells by using a potent LpxC inhibitor -LPC-011. We first determined the susceptibility of C. burnetii LpxC to LPC-011 in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…In our attempts to culture C. burnetii in regular CO 2 incubators (∼20% oxygen), we found that a C. burnetii Nine Mile phase II transformant-NMII pMMGK can grow robustly (∼3 logs increase) if starting from a reasonably high inoculum concentration in the regular ACCM-2 medium (without tryptophan supplementation) (Figure 1A). The pMMGK plasmid is composed of the pMMB207 backbone (a RSF1010 ori and a repABC operon), an eGFP gene and a kanamycin resistance cassette (10). This initial finding of C. burnetii normoxic growth was made in T-flask cultures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our attempts to culture C. burnetii in regular CO 2 incubators (∼20% oxygen), we found that a C. burnetii Nine Mile phase II transformant-NMII pMMGK can grow robustly (∼3 logs increase) if starting from a reasonably high inoculum concentration in the regular ACCM-2 medium (without tryptophan supplementation) (Figure 1A). The pMMGK plasmid is composed of the pMMB207 backbone (a RSF1010 ori and a repABC operon), an eGFP gene and a kanamycin resistance cassette (10). This initial finding of C. burnetii normoxic growth was made in T-flask cultures.…”
Section: Resultsmentioning
confidence: 99%
“…The pMMGK plasmid is composed of a RSF1010 ori, a repABC operon, an eGFP gene and a kanamycin resistance cassette. Construction of pMMGK was described previously (10).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…C. burnetii transformants were expanded in ACCM-2, suspended in SPG (0.25M sucrose, 10mM sodium phosphate, 5mM L-glutamic acid) and kept frozen at −80°C. Genome copy numbers were determined by Taqman probe qPCR specific to dotA [53].…”
Section: Methodsmentioning
confidence: 99%
“…Total DNAs were extracted with DNeasy Blood Tissue Kit (Qiagen). Genome copy numbers of C. burnetii in both axenic and cell cultures were determined by Taqman probe qPCR as previously described [53]. PCR conditions were as follows: initial denaturation at 94°C for 10min, followed by 40 cycles of amplification at 94°C for 15 s, 60°C for 1min.…”
Section: Methodsmentioning
confidence: 99%